Determination of Heavy metals in Candy Sold at School in Vientiane Capital - PHONGSAVATH, Sengthavy; CHOUNLAMANY, Vanseng; PHOUTHAVONG, Vanpaseth (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research aimed to determine of Heavy metals, namely, Cadmium (Cd), Lead (Pb), Chromium (Cr), Copper (Cu), Manganese (Mn), Zinc (Zn) in 45 candy samples which were manufactured in foreign countries. These candies samples can be found for sale in schools and grocery stores in Vientiane Capital. The samples were decomposed in a solution with HNO3 65% and H2O2 30%. The contaminant elements were measured with Atomic Absorption Spectrophotometer. The percent recovery of heavy metals was 85 -112 %. The forty-five candy samples contained Cd between 0.07 ‒ 16.05 ± 0.01 mg/kg, Pb between 0.25-22.36 ± 0.18 mg/kg, Cu between 0.02‒19.65 ± 0.01 mg/kg, Cr between 0.16 - 46.71 ± 0.43 mg/kg, Zn between 0.16-7.35 ± 0.12 mg/kg and Mn between 0.07 - 17.15 ± 0.09 mg/kg. According to the analysis, 50% of all samples was found to be contaminated with the heavy metals. Most of the contamination levels were above the MAL of each heavy metal, particularly for Cd, Pb.